The Disengagement Phenomenon of Terrorist from the Fundamental Groups and Radical Terrorists in Lamongan, East Java Indonesia - Ishomuddin, Ishomuddin; Ahmad, Miqdad Daly; Roshanti, Dian; Nurwatari, Dewi (Technium Social Sciences Journal, 2022)
Disengagement from terrorism in English is called disengagement is an attempt to divorce from radical movements and terrorism. Terrorism arises because of the problem of radical-fundamental understanding that exists in a group of Islamic societies. Prevention efforts have been carried out by both the government and the private sector. This study aims to: (1) to find out the phenomenon of disengagement of terrorist criminals from radical terrorist groups. And second, to know the process of disengagement of terrorist criminals from radical terrorist groups. This study uses a social definition paradigm, a qualitative approach, with a phenomenological type of research. The results are expected to find propositions related to the disengagement phenomenon of terrorist criminals.